How to become a luxury brand? : the case of three wine companies - Petronio, Margot Léa (2020)
The aim of this dissertation is to understand how wine brands can ascend into the highest tiers of luxury. The research focuses on how to create a luxury wine brand when luxury is based on heritage and tradition. To answer our research question, we focus on the luxury wine industry, which is a growing niche segment of the luxury sector. A qualitative data approach was adopted, and a multiple case study was conducted about one French and two Portuguese, family-owned companies: Niepoort Vinhos, Champagne Jacques Selosse, Vinhos Barbeito. Although unique in their kinds, these companies present many similarities regarding their size and structure, history and values, but essentially and fundamentally, the philosophy and strategy these businesses employed to create a luxury brand from scratch were very comparable and unveil many convergences worthy of a case study. The findings show that there are many strategies and set of actions that enable wine brands to ascend into the highest tiers of luxury. The quest for elitism through a distinctive positioning, inducing desirability by creating rarity, challenging the status quo and a last but not least, having a luxury marketing mix.